2003
DOI: 10.1007/s00199-002-0327-2
|View full text |Cite
|
Sign up to set email alerts
|

Implementation in teams

Abstract: This paper considers a team production model in which the final output is a function of one or more observable intermediate variables that are functions of the actions of the team members. When there is only one intermediate variable, our model essentially reduces to the standard models in which only the final output is observable. We provide a necessary and sufficient condition for implementing an outcome. This condition imposes restrictions on the possible deviations from the outcome that can be caused by ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Casual observation suggests that in reality the 6 If in the case of unilateral shirking it is possible to identify some team within the partnership that contains the (unique) shirker, then it may be possible to implement the efficient outcome. This is discussed in Nandeibam (2003). 7 For other solutions to the problem see, e.g., Rasmusen (1987), Legros and Matsushima (1991) and d'Asperment and Gérard-Varet (1998). opposite is true.…”
Section: Partnership Puzzlesmentioning
confidence: 99%
“…Casual observation suggests that in reality the 6 If in the case of unilateral shirking it is possible to identify some team within the partnership that contains the (unique) shirker, then it may be possible to implement the efficient outcome. This is discussed in Nandeibam (2003). 7 For other solutions to the problem see, e.g., Rasmusen (1987), Legros and Matsushima (1991) and d'Asperment and Gérard-Varet (1998). opposite is true.…”
Section: Partnership Puzzlesmentioning
confidence: 99%
“…There are several di¤erences between our model and Holmstrom's, the most important being that in our model agents produce an intermediate input that is contractible. As has been shown by Nandeibam (2002) 6 When some aspects of performance are rewarded but others are not, other types of dysfunctional behavior are possible, see Holmstrom and Milgrom (1991). This literature is surveyed in Gibbons (1998) and Prendergast (1999 (Skaperdas and Grofman [1995]).…”
Section: Introductionmentioning
confidence: 98%
“…3 Sen (1966) showed that a particular mix of the egalitarian and the proportional sharing rules achieves e¢ ciency when all agents are identical. However, when agents are not identical and inputs are heterogeneous, Browning (1983) showed that the contribution mechanism described above achieves e¢ ciency only when the production function ful…lls 1 For moral hazard problems see Holmstrom (1982) and Nandeibam (2003). 2 They also show that in "classical" economies these allocations exist.…”
Section: Introductionmentioning
confidence: 99%